Crosses on the ballot : patterns of British voter alignment since 1885 - Wald, Kenneth D. (Princeton, New Jersey : Princeton University Press, 1983)
In an exploration of mass voter alignments in Great Britain, Kenneth D. Wald illuminates the electoral consequences of major social divisions and the relationship between social structure and partisanship. He establishes that the transition from religion to social class as the chief influence on British voting occurred after World War I, as most scholars have presumed, rather than before the War, as a number of recent revisionist discussions have claimed. Originally published in 1983. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.
Frontmatter -- Contents -- Tables -- Preface -- Chapter 1. The Context of the Study -- Chapter 2. Class Politics without Class Parties? -- Chapter 3. Crosses on the Ballot? -- Chapter 4. The Methods of Analysis -- Chapter 5. Voting and Social Structure: Conceptual Problems -- Chapter 6. Voting and Social Structure: Empirical Analysis -- Chapter 7. Religious Beliefs and Political Behavior -- Chapter 8. Transformation of the Party System -- Chapter 9. Conclusion -- Select Bibliography -- Index -- Backmatter.
Includes bibliographical references and index.
Print version record.
In English.
JSTOR
Keywords: Elections -- Great Britain -- History; Voting -- Great Britain -- History; Religion and politics -- Great Britain -- History; Social classes -- Great Britain -- History; Political parties -- Great Britain -- History; Élections -- Grande-Bretagne -- Histoire; Vote -- Grande-Bretagne -- Histoire; Religion et politique -- Grande-Bretagne -- Histoire; Classes sociales -- Grande-Bretagne -- Histoire; POLITICAL SCIENCE -- Political Process -- Elections; POLITICAL SCIENCE -- Political Process -- General; Elections; Political parties; Religion and politics; Social classes; Voting; Great Britain; History